COMPARISONS OF BENCE-JONES PROTEINS AND L POLYPEPTIDE CHAINS OF MYELOMA GLOBULINS AFTER HYDROLYSIS WITH TRYPSIN - Schwartz, J. H. (The Rockefeller University Press, 1963)
L polypeptide chains of myeloma globulin and Bence-Jones protein isolated from the same patient were found to be identical after comparison of their tryptic hydrolysates by two-dimensional high voltage electrophoresis. The patterns of peptides from proteins belonging to antigenic group I differed markedly from those of proteins in antigenic group II. A partially purified H chain fraction was compared with L chains from the same myeloma protein. The tryptic hydrolysates yielded dissimilar patterns of peptides. These data indicate that γ-myeloma proteins contain two kinds of polypeptide chains, Hγ chains and either L(I) or L(II) chains. The L chains appear to be identical with those comprising the Bence-Jones protein from the same patient.